What is the Physical Fitness Level of Basketball Extracurricular Participants? Investigation of Bengkulu State Middle School 14 Students - Septian Raibowo; Vega Mareta Sceisarriya; Miftah Fajrin Rahmi; Yarmani Yarmani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The aim of this research was to determine the level of physical fitness in extracurricular participants, namely basketball. This type of research is a descriptive quantitative survey method. The population in the study was 55 people, the sampling technique used to determine the sample was purposive sampling, totaling 35 male students. The instrument used is the TKJI test for ages 13-15 years. The results obtained were that the physical fitness of basketball extracurricular participants was deficient (74.29%) with 26 students. These results can be a reference for teachers and trainers to be able to create measurable and targeted training programs and for parents to pay attention to children's nutritional patterns and daily activities. Given the significance of physical fitness for pupils, PJOK teachers in schools need to give this particular consideration while implementing in-class instruction. It will be simpler for teachers to deliver training materials or learning materials if they are physically fit, according to the conversation that has been described